Morte no trânsito não é acidente: análise e recomendações ao programa do governo de Goiás para reduzir as mortes no trânsito - Fernandes, Amauri Monge (2016)
This research was developed in order to make a diagnosis and propose recommendations for the State of Goiás to reach the goal of 20% reduction in deaths from traffic accidents by 2018, under the 'Programa Trânsito com Vida' (Traffic with Life Program), one of the basis of the Program 'Goiás Mais Competitivo'. In this thesis, it will be identified, specifically, the main causes of road accidents fatalities, to point out which actions should be a priority for its reduction and identify the role and impact of campaigns focused on traffic education. The document provides an overview about the global initiatives, regional and national on this regard, and shows how the Brazilian's behavior has a direct influence on fatal road accidents. Through field research and interviews with various actors of the traffic system, it was possible to contextualize causes, factors and consequences of road accidents in the State of Goiás. Finally, this paper presents recommendations to reduce fatal road accidents by 20%, with the practice of better public management of data, actions and resources, which are currently already available. It is noticed that it is possible to establish a process around a safe road, by leveraging coordination and alignment, among others, key success factors.